2003
DOI: 10.1159/000074240
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for the Mechanisms Underlying the Effects of Pimaradienoic Acid Isolated from the Roots of <i>Viguiera arenaria </i>on Rat Aorta

Abstract: The present study examines the effects of the diterpene ent-pimara-8(14),15-dien-19-oic acid (PA) on rat thoracic aorta. PA (10–5, 3 × 10–5 and 10–4 mol/l) caused concentration-dependent inhibition of phenylephrine (Phe)-induced contraction in either endothelium-intact or endothelium-denuded aortic rings. PA attenuated the contraction induced by CaCl2 in Ca2+-free solution containing Phe (10–7 mol/l) or KCl (30 mmol/l). This diterpene did not in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
25
0
4

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 14 publications
5
25
0
4
Order By: Relevance
“…A. cordata has been reported to possess antioxidant principles such as those of diterpenes and triterpenes (35,36), suggesting that inhibition of Aβ(25-35)-induced neuronal death by A. cordata might be due to their ROS-scavenging activity. Furthermore, diterpenes and triterpenes have been demonstrated to inhibit Ca 2+ entry through Ca 2+ channels (37,38), indicating that these compounds, including oleanolic acid, may contribute to the inhibitory activity of A. cordata on Ca 2+ entry through VDCC-and/or NMDA-receptor-coupled channels to inhibit Aβ(25-35)-induced neuronal death. Further study to elucidate the precise mechanism should be performed.…”
Section: +mentioning
confidence: 99%
“…A. cordata has been reported to possess antioxidant principles such as those of diterpenes and triterpenes (35,36), suggesting that inhibition of Aβ(25-35)-induced neuronal death by A. cordata might be due to their ROS-scavenging activity. Furthermore, diterpenes and triterpenes have been demonstrated to inhibit Ca 2+ entry through Ca 2+ channels (37,38), indicating that these compounds, including oleanolic acid, may contribute to the inhibitory activity of A. cordata on Ca 2+ entry through VDCC-and/or NMDA-receptor-coupled channels to inhibit Aβ(25-35)-induced neuronal death. Further study to elucidate the precise mechanism should be performed.…”
Section: +mentioning
confidence: 99%
“…[23] Many reports have extensively shown that terpenoids exert significant cardiovascular effects. [242526] It has also been reported that some classes of diterpenes showed significant systemic hypotensive and coronary vasodilatory effects accompanied by gradual decrease in heart rate. [2728] Saponins are also known to have several physiologic activities, depending on their chemical structures, such as hemolytic properties, alteration of membrane permeability, particularly the modulation of renal sodium excretion.…”
Section: Discussionmentioning
confidence: 99%
“…PA exerts anti-inflammatory activity, inhibiting cyclooxygenase-2 [4,5], and has been shown to inhibit contraction induced by potassium chloride (KCl) and phenylephrine in rat thoracic aorta [6]. PA can also block Ca 2+ influx through interference with both voltage-and receptor-operated channels, but is more selective in inhibiting extracellular Ca 2+ influx through voltage-dependent channels [7]. More recently, significant …”
Section: Introductionmentioning
confidence: 99%